PENGEMBANGAN USAHA PERIKANAN IKAN TONGKOL MELALUI DIVERSIFIKASI PRODUK OLAHAN BEKU MENGGUNAKAN METODE HURDLE TECHNOLOGY - Hatiningsih, S.; Harsojuwono, B.A.; Darmayanti, L.P.T.; Widiastuti, R.S. (Buletin Udayana Mengabdi; Vol 24 No 1 (2025): Buletin Udayana MengabdiDO - 10.24843/BUM.2025.v24.i01.p05, 2024)
Kedonganan Village is one of the villages producing marine fish in Bali. Kedonganan Village is one of the villages in Kuta sub-district, Badung regency. Tuna fish is a marine fish commodity that is widely found in Kedonganan Village. On the other hand, the Covid-19 pandemic has provided various changes in all areas of life in Bali, especially the economy. Many private businesses in Bali such as restaurants and hotels reduction or suffered losses. This correlates with a decrease in consumer demand for marine fish, especially tuna fish. Therefore, support is needed from various parties to solve the impact of Covid-19. One of them is through the community devotion program organized by the Udayana University and carried out by lecturers. This community devotion activity aims to provide information, knowledge, and appropriate technology in developing fishery business from fresh tuna fish to frozen food products to the community in Kedonganan Village. The result of dedication shown that the developing fishery business from fresh tuna fish to frozen food products has been going well. People of Kedonganan Village, especially the fishermen groups were very enthusiastic in following the training and assistance. Based on the result of the evaluation, they argue that the activity is beneficial to the community because it can increase information and improve the knowledge of the community. Keywords: Kedonganan Village, pandemic Covid-19, tuna fish, frozen food